On application of asymmetric Kan-like exact equilibria to the Earth magnetotail modeling - D. B. Korovinskiy; D. I. Kubyshkina; V. S. Semenov; M. V. Kubyshkina; N. V. Erkaev; N. V. Erkaev; S. A. Kiehas (Annales Geophysicae, 2018)
A specific class of solutions of the Vlasov–Maxwell equations, developed by means of generalization of the well-known Harris–Fadeev–Kan–Manankova family of exact two-dimensional equilibria, is studied. The examined model reproduces the current sheet bending and shifting in the vertical plane, arising from the Earth dipole tilting and the solar wind nonradial propagation. The generalized model allows magnetic configurations with equatorial magnetic fields decreasing in a tailward direction as slow as 1∕x, contrary to the original Kan model (1∕x3); magnetic configurations with a single X point are also available. The analytical solution is compared with the empirical T96 model in terms of the magnetic flux tube volume. It is found that parameters of the analytical model may be adjusted to fit a wide range of averaged magnetotail configurations. The best agreement between analytical and empirical models is obtained for the midtail at distances beyond 10–15 RE at high levels of magnetospheric activity. The essential model parameters (current sheet scale, current density) are compared to Cluster data of magnetotail crossings. The best match of parameters is found for single-peaked current sheets with medium values of number density, proton temperature and drift velocity.